2018
DOI: 10.1101/364125
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transgenic Zebrafish Models Reveal Distinct Molecular Mechanisms for Cataract-linked αA-Crystallin Mutants

Abstract: Mutations in the small heat shock proteins a-crystallins have been linked to autosomal dominant cataracts in humans. Extensive studies in vitro have revealed a spectrum of alterations to the structure and function of these proteins including shifts in the size of the oligomer, modulation of subunit exchange and modification of their affinity to client proteins. Although mouse models of these mutants were instrumental in identifying changes in cellular proliferation and lens development, a direct comparative an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Despite the recent progress in reducing the incidence and severity of cataract in young adult cultured lumpfish, there is still a lack of understanding of the development of cataract of the ocular tissues in these animals. There is a growing literature of pathobiology of experimentally induced cataract in models created in zebrafish ( Danio Rerio ) (Chhetri, Jacobson, & Gueven, ; Krall et al, ; Posner, McDonald, Murray, & Kiss, ; Prior, Letwin, Tuininga, & Nguyen, ; Tschopp et al, ; Wu, Zou, Mishra, & Mchaourab, ). However, there have been no pathobiological studies reported on lenticular anomalies in lumpfish.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the recent progress in reducing the incidence and severity of cataract in young adult cultured lumpfish, there is still a lack of understanding of the development of cataract of the ocular tissues in these animals. There is a growing literature of pathobiology of experimentally induced cataract in models created in zebrafish ( Danio Rerio ) (Chhetri, Jacobson, & Gueven, ; Krall et al, ; Posner, McDonald, Murray, & Kiss, ; Prior, Letwin, Tuininga, & Nguyen, ; Tschopp et al, ; Wu, Zou, Mishra, & Mchaourab, ). However, there have been no pathobiological studies reported on lenticular anomalies in lumpfish.…”
Section: Introductionmentioning
confidence: 99%